Isolation and characterization of naïve follicular dendritic cells - Usui, Kenta; Honda, Shin-ichiro; Yoshizawa, Yuichi; Nakahashi-Oda, Chigusa; Tahara-Hanaoka, Satoko; Shibuya, Kazuko; Shibuya, Akira (Molecular immunology, 2012)
► We established a novel method for FDC isolation from the spleen of naïve mice. ► Naïve FDC is can be isolated as by sorting CD45−, FDC-M2+ and ICAM-1+ cells from the spleen by flow cytometry. ► Isolated FDC supported B cells proliferation via BAFF. Follicular dendritic cells (FDC) are specialized antigen-presenting cells to cognate B cells in the follicle of the lymphoid tissues. FDC also support survival and proliferation of the B cells, leading to the germinal center formation. FDC therefore play a central role in humoral immune responses. However, molecular and functional characteristics of FDC are largely unknown, because it is difficult to isolate and analyze FDC due to a very small number of FDC in the lymphoid tissues and the fragility by mechanical and chemical stresses in vitro. In this report, we established a novel method for FDC isolation from the spleen of naïve mice by flow cytometry and analyzed the phenotypical and functional characteristics. The isolated FDC, which accounted for ∼0.2% of the spleen cells of naïve mice, were CD45−, FDC-M2+, and ICAM-1+, and supported the survival and LPS-induced proliferation of B cells. We also showed that a neutralizing antibody against B cell activating factor TNF family (BAFF) suppressed FDC-dependent B cell proliferation in the presence of LPS, but not survival, demonstrating the evidence that FDC-derived BAFF is involved in B cell proliferation.